Random Mixture Agroforestry Pattern: Economic Value for the Engkangin Village Community - Emi Roslinda; Bella Talita; Togar Fernando Manurung (Forest and Nature, 2026)
Traditional agroforestry systems developed by local communities play an important role in sustaining livelihoods and reducing pressure on protected forests, yet their economic significance and structural characteristics remain under-documented. This study analyzes the structure, composition, and livelihood contribution of a traditional random-mixture agroforestry system practiced by forest-adjacent communities in Engkangin Village, West Kalimantan, Indonesia. Data were collected in February 2025 through field observations and structured interviews with 68 agroforestry households and analyzed using descriptive and income-based approaches. The system represents a forest-based agroforestry model characterized by a non-systematic spatial arrangement integrating perennial trees, plantation crops, annual crops, and aquaculture components (agrisilviculture and agrosilvofishery). Fifteen commercial commodities were identified, dominated by paddy, oil palm, and rubber. Agroforestry generated a total annual economic value of IDR 2.89 billion. Net agroforestry income accounted for 94.22% of total household earnings, indicating a high dependence on this land-use system for livelihood security. The diversified species composition enables continuous harvests across temporal scales, enhancing income stability and food availability while maintaining tree cover in protected forest landscapes. However, the random spatial configuration limits productivity and management efficiency compared with more structured agroforestry designs. The findings demonstrate that traditional mixed agroforestry can function as a socio-ecological safety net and a locally adapted strategy for sustainable land use. Strengthening technical support, improving planting materials, and enhancing market access could substantially increase both economic returns and ecological benefits. These results provide evidence for integrating community-based agroforestry into rural development and forest conservation policies in tropical regions.